Efficacy of ABC-X model care intervention combined with omalizumab on moderate to severe allergic asthma and negative emotional of family members - ZHAO Nina; YUE Xueyan; RU Liang (Yixue xinzhi zazhi)
Objective To explore the clinical efficacy of ABC-X model intervention combined with omalizumab on moderate to severe allergic asthma (AA) and negative emotions of family members.  Methods AA children and their families from the First Affiliated Hospital of Xinjiang Medical University from January 2022 to January 2023 were prospectively recruited in the research. According to the random number table method, AA children and their families were divided into ABC-X group (ABC-X model care intervention combined with omalizumab) and routine group (usual care combined with omalizumab). Observe and compare clinical efficacy before and after intervention, incidence of adverse reactions to omalizumab, pulmonary function, immune function, inflammatory indicators, and negative emotions of family members.Results A total of 120 children with asthma and their families were recruited in the study, with 60 pairs in each group. Before the intervention, C-ACT scores, lung function, immune function, inflammatory indicators, SAS scores and SDS scores showed no statistically significant differences between the ABC-X and conventional groups (P>0.05). After 16 weeks of intervention, in terms of clinical efficacy and safety in children with AA, the total response rate and C-ACT rate in the ABC-X group were significantly higher than the conventional group after intervention (P0.05). In terms of family negative emotions, SAS and SDS scores decreased significantly compared with before intervention (P